Analysis of Poverty and Inequality in Bolivia,1999-2005: A Microsimulation Approach - Claudia Gutierrez (Institute for Advanced Development Studies (INESAD), 2008)
This paper studies the changes in inequality and poverty in the period 1999-2005 in Bolivia through the analysis of the changes in the labour market. A decomposition method based on micro-simulation techniques was applied. The decomposition works with an income generation model at the household level, which is a set of equations for the individual earnings and for the labour supply and occupational choices for each member of the household. We decomposed the observed change in inequality into four components: i) a shift in the income distribution related to a change in employment rates and the shares of wage and non-wage labour among the employed population (participation effect); ii) a shift related to changes in the remuneration of observed characteristics of the employed population (price effect); iii) a shift related to a change in the distribution of error terms of estimated earn-ings functions (error term effect); and iv) a residual change in inequality not cap-tured by the first three simulated changes in the income distribution. According to our results the increase in inequality of 3 points of the Gini coefficient, was ex-plained by approximately 1 point for the participation, price and error term effects and 2 points for the residual change. The increase in the unemployment rate, the shift in the participation of the non wage earners, the rise in wages and the more unequal distribution of unobserved productive talents deteriorated the income dis-tribution in this period in Bolivia. Regarding the poverty incidence, the observed variation was a reduction by 3 points explained mainly by the residual change. The low magnitude of the simulated effects as determinants of the decline in poverty in those years can be explained by the rising participation of the non labour incomes in the total household income.
Keywords: O54; R20; P46; 330; Poverty; Inequality; Microsimulation; Bolivia